The Compliance Level of Social Media Influencers in Fulfilling Income Tax Obligations in Riau Province - M. Raihan Fadillah; Yusralaini Yusralaini; Supriono Supriono (Universitas Negeri Semarang, 2022)
Purpose : The study examines and analyzes the influence of tax knowledge, tax sanctions, and the quality of tax services on social media influencer taxpayer compliance in Riau province. Method : The population in this study is social media influencers in Riau province. The sample in this study was 85 social media influencer accounts in Riau province following predetermined criteria. The data used in this study is primary data using a questionnaire as a data collection tool, and the questionnaires were tested for validity and reliability before collecting research data. The data analysis technique in this study uses the classical assumption test, multiple linear regression analysis. Findings : The results of this study indicate that the variables of tax knowledge, tax sanctions, and tax service quality have a positive and significant effect on taxpayer compliance with Social Media Influencers in Riau province Novelty : The research is classified as new research because it shows how the tax compliance of a social media influencer in Riau province. Keywords : Taxpayer Compliance; Tax Knowledge; Tax Sanctions; Tax Service Quality; Social Media Influencers